Effect of Heat Treatment and Titanium Addition on the Microstructure and Mechanical Properties of Cast Fe31Mn28 Ni15Al24.5Tix High-Entropy Alloys - Shimaa El-Hadad; Mervat Ibrahim; Mohamed Mourad (Advances in Materials Science and Engineering)
High-entropy alloys (HEAs) are multiprincipal element alloys with controllable properties. Studying the mechanical properties of these alloys and relating them to their microstructures is of interest. In the current investigation, Fe31Mn28 Ni15Al24.5Tix high-entropy alloys with Ti content (0–3 wt.%) were prepared by casting in an induction furnace. Different heat treatments were applied, and the microstructure and hardness of the cast samples were studied. It was observed that addition of up to 3.0 wt.% Ti significantly increases the hardness of the alloy from 300 to 500 (Hv) by the combined effect of solid solution strengthening and via decreasing lamellar spacing. Heat treatment at 900°C for 10 h enhanced the hardness at lower Ti percentages (0.0–0.8 wt.%) by decreasing the lamellar spacing, while no change was observed at higher Ti content. It was also observed that extending the treatment time to 20 h affected negatively the hardness of the alloy. Concluding, HEAs can achieve high hardness using low-cost principle elements with minor alloying additives compared to the other traditional alloys.